Air-stable, recyclable, and time-efficient diphenylphosphinite cellulose-supported palladium nanoparticles as a catalyst for Suzuki–Miyaura reactions - Du, Qingwei; Li, Yiqun (Beilstein Journal of Organic Chemistry, 2011)
A diphenylphosphinite cellulose palladium complex (Cell–OPPh2–Pd0) was found to be a highly efficient heterogeneous catalyst for the Suzuki–Miyaura reaction. The products were obtained in good to excellent yield under mild reaction conditions. Moreover, the catalyst could be easily recovered by simple filtration and reused for at least 6 cycles without losing its activity.
Keywords: diphenylphosphinite cellulose; heterogeneous catalysis; nanopalladium; polymer-supported catalyst; Suzuki–Miyaura reaction